Barrier and Facilitators of HIV Related Risky Sexual Behavior - Soheila Asgari; Saharnaz Nedjat; Ameneh Setareh Forouzan; Ashkan Shahnazi; Reza Majdzadeh (Tehran University of Medical Sciences, 2013)
Background: This study was conducted to identify the determinants of protective behavior in relation to HIV transmission. Since the risk of transmission is higher among those who have extramarital intercourse, the study sample constituted of such people.Methods: We started this study in 2010 and finished it in 2011. Participants were divided into low-risk and high-risk groups. High-risk people included sex workers and those who presented at drop-in centers. Interviewees were 18 men and women in the low-risk group and 12 men and women in the high-risk group. Data were collected through in-depth interviews and were analyzed using the thematic framework method.Results: In both groups, protective behavior was influenced by willingness to protect, intention or decision to protect, and personal, social, and environmental barriers and facilitators. In terms of willingness, behavior was influenced to preserve sexual pleasure by avoiding condoms. In terms of barriers and facilitators, trust in partner, misperceptions, condom inaccessibility, unplanned sex, fear of contracting the disease, partner's wish, ethical commitments were mentioned by both groups, stigma of condom possession by the low-risk group, and partner's force was mentioned by the high-risk group.Conclusion: Educational programs need to focus on changing the concept that "condoms reduce sexual pleasure". In addition, interventional programs to strengthen factors such as self-efficacy, ethical commitments, faithfulness, and correct beliefs such as undue trust in partner, misconception of being safe, unplanned sex, and the stigma of possessing condoms can be very effective in changing high-risk sexual behavior.